Automated Processing of Plasma Samples for Lipoprotein Separation by Rate-Zonal Ultracentrifugation - Peters, Carl N.; Evans, Iain E. J. (Journal of Laboratory Automation, 2016)
Plasma lipoproteins are the primary means of lipid transport among tissues. Defining alterations in lipid metabolism is critical to our understanding of disease processes. However, lipoprotein measurement is limited to specialized centers. Preparation for ultracentrifugation involves the formation of complex density gradients that is both laborious and subject to handling errors. We created a fully automated device capable of forming the required gradient. The design has been made freely available for download by the authors. It is inexpensive relative to commercial density gradient formers, which generally create linear gradients unsuitable for rate-zonal ultracentrifugation. The design can easily be modified to suit user requirements and any potential future improvements. Evaluation of the device showed reliable peristaltic pump accuracy and precision for fluid delivery. We also demonstrate accurate fluid layering with reduced mixing at the gradient layers when compared to usual practice by experienced laboratory personnel. Reduction in layer mixing is of critical importance, as it is crucial for reliable lipoprotein separation. The automated device significantly reduces laboratory staff input and reduces the likelihood of error. Overall, this device creates a simple and effective solution to formation of complex density gradients.